2008
DOI: 10.1159/000177916
|View full text |Cite
|
Sign up to set email alerts
|

Can Comprehensive Stroke Centers Erase the ‘Weekend Effect’?

Abstract: Background: Prior epidemiological work has shown higher mortality in ischemic stroke patients admitted on weekends, which has been termed the ‘weekend effect’. Our aim was to assess stroke patient outcomes in order to determine the significance of the ‘weekend effect’ at 2 comprehensive stroke centers. Methods: Consecutive stroke patients were identified using prospective databases. Patients were categorized into 4 groups: intracerebral hemorrhage (ICH group), ischemic strokes not treated with IV t-PA (intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 30 publications
10
91
1
2
Order By: Relevance
“…20,32 The "weekend effect" has been eliminated in comprehensive centers with around-the-clock availability of neurologists, neurosurgeons, and intensivists. 1,29 This is in agreement with the observed positive effect of more neuroscience providers in decreasing stroke mortality rates in the current analysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…20,32 The "weekend effect" has been eliminated in comprehensive centers with around-the-clock availability of neurologists, neurosurgeons, and intensivists. 1,29 This is in agreement with the observed positive effect of more neuroscience providers in decreasing stroke mortality rates in the current analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Several lines of evidence point to the value of access to appropriate health systems in the outcomes after stroke. 1,13,29 Along the same lines, telemedicine and telestroke care is increasingly used to provide timely care in stroke patients. 8,9,28 Recent studies have demonstrated increased stroke-related mortality during the weekends, potentially due to the decreased availability of specialized care providers.…”
Section: Discussionmentioning
confidence: 99%
“…No such difference in mortality was observed at CSCs on weekends versus weekdays. In another study of 2 CSCs, 23 a total of 2211 adult patients were included. Patients were categorized into 4 groups: an intracerebral hemorrhage group, an arterial IS group not treated with intravenous tissue-type plasminogen activator, an arterial IS treated with tissue-type plasminogen activator, and a transient ischemic attack group.…”
Section: Discussionmentioning
confidence: 99%
“…15 This lack of a "weekend effect" is felt to be related to the 24/7 availability of stroke specialists, advanced neuroimaging, ongoing training, and surveillance of specialized nursing care available at CSCs. 4,16 In our study, New Jersey CSCs overall had significantly higher rates of thrombolysis compared to PSCs (19.5% vs 9.6%) when looking at the 3-hour window. This is higher overall than the national rate of 3.4% to 5.2%.…”
Section: Discussionmentioning
confidence: 56%